2006
DOI: 10.1039/b603665a
|View full text |Cite
|
Sign up to set email alerts
|

IRMPD spectroscopy of metal-ion/tryptophan complexes

Abstract: Infrared multiple-photon dissociation (IRMPD) spectroscopy is employed to obtain detailed binding information on singly charged silver and alkali metal-ion/tryptophan complexes in the gas phase. For these complexes the presence of the salt bridge (i.e. zwitterionic) tautomer can be virtually excluded, except for perhaps a few percent in the case of Li+. Two low-energy structures having the charge solvation form are shown to be likely, where the metal cation is either in a tridentate N/O/Ring conformation or in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
241
1
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 165 publications
(262 citation statements)
references
References 57 publications
18
241
1
2
Order By: Relevance
“…† Such similarities have previously been reported for the IR spectra of Ag + and Li + complexes with other bioorganic molecules, such as arginine and tryptophan. 24,25 Indeed, the calculated binding free energies are quite similar for the O4 complexes of Li + LC and Ag + LC (272 and 262 kJ mol À1 ), which explains the similar impact of the metal ion complexation on the CQO4 bond properties. However, the metal ligand bond distances are quite different in both complexes.…”
Section: Ag + Lcmentioning
confidence: 69%
See 1 more Smart Citation
“…† Such similarities have previously been reported for the IR spectra of Ag + and Li + complexes with other bioorganic molecules, such as arginine and tryptophan. 24,25 Indeed, the calculated binding free energies are quite similar for the O4 complexes of Li + LC and Ag + LC (272 and 262 kJ mol À1 ), which explains the similar impact of the metal ion complexation on the CQO4 bond properties. However, the metal ligand bond distances are quite different in both complexes.…”
Section: Ag + Lcmentioning
confidence: 69%
“…This combined strategy has proven to be a powerful tool to characterize metal ion complexes of a large variety of (bio-)molecules. [21][22][23][24][25][26][27][28][29][30][31][32][33] Similar to protonated flavins, 18 the CO stretch modes serve as the main indicator of the metal binding sites. The comparison of the measured IRMPD spectra with the calculated linear absorption spectra provides insight into their respective structures and bonding mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study [27], it was shown from the IR spectrum of nondeuterated [Trp ϩ K] ϩ (Figure 1a, black trace) that the population consists of two CS conformers, tridentate N/O/Ring (50 -60%) and bidentate O/Ring (40 -50%), and that there is no observable presence of ZW (for structures see Scheme 1). This is not surprising, as N/O/Ring (ϩ1 kJ mol Ϫ1 ) and O/Ring (0 kJ mol Ϫ1 ) are almost isoenergetic, while ZW is much less favorable energetically (ϩ15 kJ mol Ϫ1 ).…”
Section: Resultsmentioning
confidence: 95%
“…The calculations were carried out at the DFT level (B3LYP/6-311 ϩ G(d,p)) using the Gaussian software package [33], and were zero-point energy corrected [27]. The frequencies were scaled (0.987) and a Gaussian convolution was applied (FWHM ϭ 30 cm Ϫ1 ).…”
Section: Experimental and Calculationsmentioning
confidence: 99%
“…T he combination of ion-trapping mass spectrometers and free-electron lasers tunable through the mid-infrared region of the electromagnetic spectrum have provided invaluable access to the vibrational spectra of discrete, gas-phase metal complexes [1][2][3][4][5][6][7][8][9][10]. It is generally difficult to acquire a conventional linear absorption spectrum of species commonly investigated by mass spectrometry because of the low ion concentrations.…”
mentioning
confidence: 99%